Market Power in the Philippine Domestic Shipping Industry - Kris A. Francisco; Michael Ralph M. Abrigo (Philippine Institute for Development Studies (PIDS), 2023)
High market concentration in the Philippine domestic shipping industry has always been a subject of concern among policymakers and researchers. While many reforms aimed at improving the level of competition in the industry have been implemented since the 1990s, studies show that domestic shipping operations remain in the hands of a few players, especially at the route-level. This study aims to enrich the discussion by providing an alternative measure of market power in domestic shipping, through the estimation of markups -a useful indicator of how firms can price their goods or services above marginal cost. Estimates confirm the exercise of market power in the domestic shipping industry, as evidenced by high markups. It was also found that markup on freight is relatively larger than the markups on passenger services. Additional analysis confirms that having a high market share significantly influences high markups.
Keywords: D2; D4; L1; 330; Market power; Markups; Domestic shipping